Zwint-1 is required for spindle assembly checkpoint function and kinetochore-microtubule attachment during oocyte meiosis - Woo Seo, Dong (Sci Rep, 2015)
The key step for faithful chromosome segregation during meiosis is kinetochore assembly. Defects in this process result in aneuploidy, leading to miscarriages, infertility and various birth defects. However, the roles of kinetochores in homologous chromosome segregation during meiosis are ill-defined. Here we found that Zwint-1 is required for homologous chromosome segregation during meiosis. Knockdown of Zwint-1 accelerated the first meiosis by abrogating the kinetochore recruitment of Mad2, leading to chromosome misalignment and a high incidence of aneuploidy. Although Zwint-1 knockdown did not affect Aurora C kinase activity, the meiotic defects following Zwint-1 knockdown were similar to those observed with ZM447439 treatment. Importantly, the chromosome misalignment following Aurora C kinase inhibition was not restored after removing the inhibitor in Zwint-1-knockdown oocytes, whereas the defect was rescued after the inhibitor washout in the control oocytes. These results suggest that Aurora C kinase-mediated correction of erroneous kinetochore-microtubule attachment is primarily regulated by Zwint-1. Our results provide the first evidence that Zwint-1 is required to correct erroneous kinetochore-microtubule attachment and regulate spindle checkpoint function during meiosis.